Administrative Factors Affecting Effectiveness of Schools under Secondary Educational Service Area Office Loei Nongbualamphu: Administrative Factors Affecting Effectiveness of Schools under Secondary Educational Service Area Office Loei Nongbualamphu - Kaewkam, Wilairat; Siritharo, PhrakrupaladChakrapol (RATANABUTH JOURNAL, 2023)
The purposes of this research were 1) to study the level of administrative factors under Secondary Educational Service Area Office Loei Nongbualamphu, 2) to study the level of effectiveness of schools under Secondary Educational Service Area Office Loei Nongbualamphu, 3) to investigate the relationship between administrative factors and effectiveness of schools under Secondary Educational Service Area Office Loei Nongbualamphu, 4) to study the administrative factors affecting effectiveness of schools under Secondary Educational Service Area Office Loei Nongbualamphu and 5) to generate the equation of forecasting the administrative factors affecting effectiveness of schools under Secondary Educational Service Area Office Loei Nongbualamphu. The samples consisted of school administrators and teachers, yielding a total of 323 participants working under Secondary Educational Service Area Office Loei Nongbualamphu in the 2022 academic year. The research instrument was a set of questionaires. Statistics for data analysis were frequency, percentage, mean, standard deviation, Pearson’s product – moment correlation coefficient and Stepwise multiple regression analysis. The findings were as follows: 1) The administrative factors under Secondary Educational Service Area Office Loei Nongbualamphu as a whole was at the high level. 2) The effectiveness of schools under Secondary Educational Service Area Office Loei Nongbualamphu as a whole at the high level. 3) The relationship between administrative factors and effectiveness of schools under Secondary Educational Service Area Office Loei Nongbualamphu had a positive relationship at the .01 level of significance overall. 4)The administrative factors comprised three aspects which were able to predict the effectiveness of schools under Secondary Educational Service Area Office Loei Nongbualamphu at a statistical significance of the .01 level, in terms of Personnel development, Communication and Organization structure. The said variables were able to predict the effectiveness of schools at 74.30 percent with a standard error of estimate of ±.23629. 5) The regression equation of raw scores could be summarized and standardized scores could be written as follows: Yt′ = .659 + .325X2 + .277X7 + .259X5 ZYt′ = .341Z2 + .303Z7 + .300Z5